Effect of irradiation time on refractive index and reflectivity during growth of fiber bragg grating - Bashir Ahmad Tahir 300693; Ho, Sze Phing 326489; Jalil Alii; Roly Abdul Rahm (Skudai : Universiti Teknologi Malaysia, 2009)
Bibliography: p. 6.